Conventional doped silica/fluoride glass fibers for low loss and minimum dispersion effects - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
This paper has clarified the conventional silica doped (SiGeO2) and aluminum fluoride (AlF3) fibers for low loss and minimum dispersion effects for upgrading fiber-optic communication systems. The total dispersion with the total losses are modeled for both fibers. Fiber bandwidth and the power received are estimated based on different dopant ratios. The spectral and thermal effects are applied on both fibers. The study assured the negative effects of increasing ambient temperatures and the positive effects of increasing dopant ratios on the performance of the fibers.